2007
DOI: 10.1177/0883073807308702
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Autism Spectrum Disorder in China

Abstract: The object of this study was to investigate the epidemiologic pattern of autism spectrum disorder in Chinese children. An autism spectrum disorder registry has been established in Hong Kong since 1986 by collecting data in a single center (the only university-affiliated child assessment center in Hong Kong). Since 1997, inpatient data from all public hospitals under the Hospital Authority have been stored in a central computerized program and retrieved from the Clinical Data Analysis and Reporting System. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 28 publications
8
65
1
5
Order By: Relevance
“…Table 1 provides a summary of the characteristics of the sample in terms of age and gender. The ratio of boys to girls is 6:1, which reflects the gender bias evident in epidemiological studies of ASD (Baron-Cohen et al, 2011;Fombonne, 1999) and is consistent with the findings reported by Wong and Hui (2008) in which the male to female ratio was found to be 6.58:1 in Hong Kong children.…”
Section: Participantssupporting
confidence: 80%
See 1 more Smart Citation
“…Table 1 provides a summary of the characteristics of the sample in terms of age and gender. The ratio of boys to girls is 6:1, which reflects the gender bias evident in epidemiological studies of ASD (Baron-Cohen et al, 2011;Fombonne, 1999) and is consistent with the findings reported by Wong and Hui (2008) in which the male to female ratio was found to be 6.58:1 in Hong Kong children.…”
Section: Participantssupporting
confidence: 80%
“…The majority of the available studies have focused on the prevalence of ASD in children and the findings have been inconsistent. In Hong Kong, Wong and Hui (2008) reported a prevalence rate of 16.1 per 10,000 for children under 15 years old, which was generally consistent with the epidemiological findings in other areas in the world (Matson & Kozlowski, 2011). However, the Hong Kong Government's estimation of the prevalence rate of ASD was on the low side (The Rehabilitation Advisory Committee, 2005).…”
Section: Introductionsupporting
confidence: 70%
“…The current education system in China provides limited opportunities for children with severe intellectual disability [14], although these children often receive some healthcare services [15]. The Chinese healthcare system is unique in that it incorporates aspects of both Western medicine and traditional Chinese medicine (TCM) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates per country can be difficult to determine. Posserud et al (2010), the Autism Society 2010, Autism Speaks 2008 and (Wong, 2007) calculated and identified respective country's approximate prevalence rates of autism diagnoses of children living in other countries throughout the world and combined as follows:…”
Section: Prevalence Rates Of Autismmentioning
confidence: 99%